SKILLS AND DUTIES OF IMPROVING THE QUALITY OF EDUCATION IN THE EDUCATION SYSTEM OF THE REPUBLIC (Web of Teachers: Inderscience Research, 2024)
This article discusses the problems of improving the quality of education today, their solutions and perspectives, including the improvement of curricula, training design, organization of research in accordance with the requirements of the time, the use of foreign experience in this area, professional qualities and the development of logical thinking operations.